2013
DOI: 10.1080/13825585.2012.738289
|View full text |Cite
|
Sign up to set email alerts
|

The influence of aging on attentional refreshing and articulatory rehearsal during working memory on later episodic memory performance

Abstract: We investigated age-related changes in two proposed mechanisms of maintenance in working memory, articulatory rehearsal, and attentional refreshing, by examining the consequences of manipulating the opportunity for each on delayed recall. Both experiments utilized modified operation span tasks to vary the opportunity for articulatory rehearsal (Experiment 1) and attentional refreshing opportunities (Experiment 2). In both experiments, episodic memory was tested for items that had been initially studied during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
80
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 41 publications
13
80
2
6
Order By: Relevance
“…The two-operation span task should allow more refreshing opportunities than the one-operation task, because one covert retrieval could occur after each operation. Whereas variation in rehearsal did not induce any difference in the delayed test, delayed-recall performance did increase with the number of refreshing opportunities (Loaiza & McCabe, 2013). The authors concluded that refreshing is important for maintaining information in both working and episodic memory.…”
Section: Refreshing Maintenancementioning
confidence: 81%
See 3 more Smart Citations
“…The two-operation span task should allow more refreshing opportunities than the one-operation task, because one covert retrieval could occur after each operation. Whereas variation in rehearsal did not induce any difference in the delayed test, delayed-recall performance did increase with the number of refreshing opportunities (Loaiza & McCabe, 2013). The authors concluded that refreshing is important for maintaining information in both working and episodic memory.…”
Section: Refreshing Maintenancementioning
confidence: 81%
“…We should nevertheless replicate the well-known detrimental effect in immediate recall when rehearsal is impeded by a concurrent articulation. In this regard, it should be noted that Loaiza and McCabe (2013) reported that rehearsal did not affect delayed recall. However, the two conditions that they contrasted both involved concurrent articulation, the amount of which varied.…”
Section: Refreshing Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…Whereas articulatory maintenance rehearsal has only a limited effect on long-term memory (Greene, 1987), refreshing has been shown to improve long-term retention (Raye et al, 2007), and providing more time for refreshing during a WM task results in better recall of the memoranda in a delayed test (Camos & Portrat, 2015;Loaiza & McCabe, 2012b) Therefore, the efficiency of refreshing could be a source of common variance of WM and long-term memory. In line with this hypothesis, Loaiza and McCabe (2012a) have argued that age differences in episodic long-term memory can in part be explained by age differences in the efficiency of refreshing.…”
Section: Correlations With Long-term Memory (C3)mentioning
confidence: 91%